2010
DOI: 10.1097/prs.0b013e3181d180e9
|View full text |Cite
|
Sign up to set email alerts
|

Facial Aesthetic Unit Remodeling Procedure for Neurofibromatosis Type 1 Hemifacial Hypertrophy: Report on 33 Consecutive Adult Patients

Abstract: The facial aesthetic unit remodeling monobloc translesional resection technique on a preestablished pattern has been reproducible, offered increased predictability in functional and cosmetic results, and allowed us to operate on extensive hemifacial lesions with a lower transfusion risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…Patients’ priorities need to be respected, as surgery in these patients is to some extent palliative. 2 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients’ priorities need to be respected, as surgery in these patients is to some extent palliative. 2 …”
Section: Discussionmentioning
confidence: 99%
“…Elephantiasis neuromatosa is a severe form of neurofibromatosis type 1 1 , 2 in which there is diffuse proliferation of Schwann cells and axons together with a bony hypertrophy, resulting in massive disfigurement. We herein report a case of this kind associated with a severely ptotic ear.…”
mentioning
confidence: 99%
“…Hypotensive anesthesia and infiltration of tumescent fluid are effective in decreasing the intraoperative bleeding. [14,15] The multi-layered hemostatic sutures permit to remove piecewise the tumor avoiding profuse bleeding in all our procedures, and is based on vessel collapse after mechanical ligation, [4] from the superficial surface to deep layers, preserving the vital structures. The stitches placed parallel to the axial pattern of the nerve branches and controlling the depth of the stitch superficial to our plane of disection makes sure that we do not trap the facial nerve branches nevertheless, some of the network interconnection between the zygomatic and buccal branch can be trapped by the suture, without affecting the facial expression.…”
Section: Discussionmentioning
confidence: 99%
“…9,14 -17 Also, it has been reported that 10% to 26% of NF-1 cases may progress to sarcomatous degeneration. 3,18,19 Only rare, well-circumscribed neurofibromas can be removed easily. However, the more common neurofi- Free-Flap Reconstruction After NF Resection broma has diffuse soft-tissue infiltration, which makes complete resection difficult.…”
Section: Discussionmentioning
confidence: 99%